RELIGIOUS FOUNDATIONS OF PATRIOTISM: ISLAM'S INFLUENCE ON LOVE FOR THE HOMELAND - Maarif, Samsul; Uyuni, Badrah; Zaini, Aceng; Idwar, Agus; Khairiyah, Nanda (Spektra: Jurnal Ilmu-ilmu Sosial, 2025)
This article delves into the intricate relationship between religion and patriotism, focusing on Islam's influence on the affection for one's homeland. It explores how Islamic teachings and beliefs have historically shaped and continue to shape the concept of patriotism among Muslims worldwide. Within Muslim-majority nations, the integration of Sharia, promotion of religious freedom, and commitment to social justice define the contours of Islamic patriotism. Moreover, the concept of Ummah coexists harmoniously with a deep-rooted sense of responsibility towards the local homeland, fostering a collective spirit of belonging and shared societal welfare. In the context of Muslim minorities residing in non-Muslim-majority countries, the study reveals a delicate balance between religious identity and active citizenship. These communities exhibit resilience and positive engagement, contributing significantly to the social fabric of their host nations while upholding Islamic principles of compassion, tolerance, and mutual respect. The research also highlights the global dimension of Islamic patriotism, emphasizing pan-Islamic solidarity and cooperation among Muslim communities worldwide. By employing a multidisciplinary approach, this study utilizes three primary research methods: literature review, ethnographic research, and the analysis of social discourse. Throughout the article, the interplay of faith and love for the homeland is explored, demonstrating the adaptability of Islamic principles to diverse social landscapes and the enduring pursuit of social harmony, justice, and unity. This comprehensive analysis contributes valuable insights into the complex interrelationship between Islam and patriotism, transcending geographical boundaries and inspiring a shared commitment to the principles of compassion and coexistence.